2012
DOI: 10.1016/j.krcp.2012.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in patients with acute kidney injury and hypotension treated with continuous veno-venous hemodiafiltration

Abstract: BackgroundContinuous veno-venous hemodiafiltration (CVVHDF) is a preferred treatment modality in hemodynamically unstable acute kidney injury (AKI) patients, because it has advantages over intermittent dialysis in terms of hemodynamic stability. However, this patient group still shows a significantly high mortality rate. To aid in the management of these high-risk patients, we evaluated the risk factors for mortality in CVVHDF-treated hypotensive AKI patients.MethodsWe studied 67 patients with AKI and hypotens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Yet our first child suffered impaired tissue perfusion associated with hemodialysis that was not related to abnormal cardiac structure or function. Despite being reported to have lesser complications CVVHDF, death complicates 11%‐16% of adult subjects on CVVHDF and hypovolemia/hypotension …”
Section: Discussionmentioning
confidence: 99%
“…Yet our first child suffered impaired tissue perfusion associated with hemodialysis that was not related to abnormal cardiac structure or function. Despite being reported to have lesser complications CVVHDF, death complicates 11%‐16% of adult subjects on CVVHDF and hypovolemia/hypotension …”
Section: Discussionmentioning
confidence: 99%
“…A more recent investigation of 197 patients requiring CRRT initiation in the ICU setting identified three independent factors associated with fatal outcomes (mechanical ventilation requirement, sepsis, and septic shock requiring vasoactive agents) and two factors associated with favorable outcomes (nonoliguric AKI and low serum creatinine levels). Finally, several study groups have attempted to identify more reliable prognostic factors associated with worse outcomes in patients with AKI, including disease severity assessed according to the APACHE II or SOFA score, amount of urine output, serum BUN level, timing of CRRT, and previous health status [ 3 - 6 , 27 - 29 ]. Despite improvements in the knowledge of such prognostic factors in patients requiring CRRT, the mortality rate of patients with AKI treated with CRRT remains high, reaching nearly 50% [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Continuous renal-replacement therapy (CRRT) has become an essential strategy for the management of critically ill patients with acute kidney injury (AKI) [ 1 , 2 ]. Previous research has identified several prognostic factors for mortality—including sepsis, higher Acute Physiology and Chronic Health Evaluation (APACHE) II score, oliguria, higher Sequential Organ Failure Assessment (SOFA) score, and the need for mechanical ventilation—in patients with severe AKI undergoing CRRT [ 3 - 6 ]. However, predicting the outcome of patients requiring CRRT remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of variables was based on identifying all measured clinical variables of known or suspected prognostic importance for mortality. The baseline variables that were assessed included demographic data (age and gender), biochemical (haemoglobin, potassium, creatinine, albumin, pH), clinical (mechanical ventilation, severe sepsis at baseline), urine output), and illness severity scores (Acute Physiology and Chronic Health Evaluation III (APACHE III) score) . A survival curve adjusted for covariates was estimated by the relevant Cox model to compare survival between the statins and non‐statin groups.…”
Section: Methodsmentioning
confidence: 99%